Comparative analysis of hepatitis B virus genotype a molecular evolution in patients infected with HBV and in patients co-infected with HBV and HIV - Cassino, Lucila (2012)
HIV infection has a significant impact on the natural progression of liver disease caused by infection with hepatitis B virus (HBV), but its role in the molecular evolution of HBV is unknown. It is difficult to study the molecular evolution of HBV longitudinally considering its genomic complexity, which implies the analysis of paired samples. This study aimed to analyze the difference in the evolutionary dynamics of HBV among patients with HIV and uninfected individuals. In this study, 17 patients infected chronically with HBV were recruited, 9 of them were co-infected with HIV. Patients were HBe antigen-positive and infected with HBV genotype A. Paired plasma samples were collected from each patient 3 years apart, and they were compared subsequently to each other. The HBV phylogenetic inference among isolates from patients infected with HBV and co-infected with HBV and HIV tends to cluster separately. Likewise, when comparing the HBV evolutionary rate and genetic distances, values were higher in the former in both preC/C and S genomic regions. Intra-host analyses of HBV isolates revealed high diversity and complexity of quasispecies among patients infected with HBV exhibiting high numbers of viral variants and genetic distance. In summary, after studying the HBV molecular evolution among isolates ascribed to genotype A at inter- and intra-host levels, HBV exhibited low quasispecies complexity and diversity as well as low evolutionary rates in the presence of HIV co-infection, suggesting that the co-infection may have an impact on the HBV molecular evolution most likely from the weakened cellular immune response.